Developing the Textbook for Teaching Arabic Using the Audiolingual to Enhance Language Skills at the Islamic Boarding School - Lubis, Zulfahmi; Lubis, Farhan Mubarok; Rozi S, Fahrur; Haq, Samsul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research aims to understand the following matters: 1) How to develop the prescribed book for teaching Arabic using the Audiolingual to enhance language skills, 2) The evaluation of linguistic and material experts regarding this book, 3) The experimental results of this book in enhancing language skills. The research methodology follows the pattern outlined by Sugiono in his book on scientific research. The researcher used testing, observation sheets, documents, and interviews to collect data. The research is conducted through the following steps: reviewing potential resources and identifying problems in the research field, collecting information about the product, designing the product according to theory, evaluating by experts, revising the product based on expert suggestions, testing the product in both the control and experimental classes and correcting the product (error correction based on some experimental feedback). For data analysis, to infer the comparison between two classes or pre- and post-teaching, statistical tests such as the paired t-test can be used. The t-test estimates the true difference between the means of two groups by comparing the difference in group means to the combined standard error of the groups. The research results indicate that the book was designed according to the theory explained by Ahmad Fouad in his book. After evaluation by both material and media experts, the book was deemed suitable for experimentation, with an 80% success rate in the trial phase. Following the experiment, the control class showed lower results than the experimental class, demonstrating that the Audiolingualis more effective and better for teaching Arabic. The success rate using this method was 88%.